Pengembangan Media Pembelajaran Games Based Learning Menggunakan Wordwall Berbasis PjBL untuk Mendukung Kemampuan Kreativitas Siswa Pada Materi Sistem Koloid: Penelitian - Bina Nurani Sibarani; Afrida; Febbry Romundza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aimed to develop and analyze the feasibility of a games-based learning medium based on Project-Based Learning (PjBL) using Wordwall with Google Sites to enhance students' creativity in colloidal system material. This study adapted Lee & Owens' Research and Development (R&D) model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, and questionnaires administered to material experts, media experts, chemistry teachers, and 10 eleventh-grade Phase F students at Nommensen High School Jambi City. The research results indicated that the developed learning medium achieved a